The Role of Macrophages in Aortic Dissection - Wang, Xinhao; Zhang, Hongpeng; Cao, Long; He, Yuan; Ma, Airong; Guo, Wei (Frontiers in Physiology, 2020)
Aortic dissection (AD) is a fatal disease that accounts for a large proportion of aortic-related deaths and has an incidence of approximately 3–4 per 100,000 individuals every year. Recent studies have found that inflammation plays an important role in the development of AD and that macrophages are the hub of inflammation in the aortic wall. Aortic samples from AD patients reveal a large amount of macrophage infiltration. The sites of macrophage infiltration and activity vary throughout the different stages of AD, with involvement even in the tissue repair phase of AD. Angiotensin II has been shown to be an important factor in the stimulation of macrophage activity. Stimulated macrophages can secrete metalloproteinases, inflammatory factors and other substances to cause matrix destruction, smooth muscle cell apoptosis, neovascularization and more, all of which destroy the aortic wall structure. At the same time, there are a number of factors that regulate macrophages to reduce the formation of AD and induce repair of torn aortic tissues. The aim of this review is to take a close look at the roles of macrophages throughout the course of AD disease.